Spatio-temporal variability of Temperature and rainfall in the Jabitehinan District in North West Ethiopia - Birhanie, Addisu Bitew; Mengistu, Daniel Ayalew (Faculty of Geography, Universitas Gadjah Mada, 2025)
Climate change, driven largely by human activities, leads to long-term shifts in temperature and precipitation. This study aimed to examine trends and spatiotemporal variability in rainfall and temperature in the Jabitehinan District, northwest Ethiopia, and assess their implications for agriculture and resource management. Historical climate data from the six meteorological stations in Ethiopian National Meteorological Agency were analyzed using Sen’s slope estimator, the Mann-Kendall test, and the Precipitation Concentration Index, while spatial variability was assessed using the Inverse Distance Weighted method. Results revealed that mean seasonal rainfall reduction trends were 0.014 mm (spring), 0.005 mm (summer), 0.207 mm (autumn), and 0.057 mm (winter), with an annual average of 0.0122 mm. Temperature trends showed consistent increases: mean seasonal values rose by 0.189°C (winter), 0.215°C (spring), 0.184°C (summer), and 0.042°C (autumn), with an annual average rise of 0.206°C. Decadal trends showed increases in maximum, minimum, and mean temperatures at rates of 0.014°C, 0.029°C, and 0.037°C, respectively. The spatial distribution of rainfall was highest in the upper highlands (1790–1890 mm/year). About 57% of the middle district received 1768–1790 mm, while 20% of the area had 1790–1812 mm, 13% had 1746–1768 mm, and 10% received 1702–1746 mm annually. These findings highlight the substantial impact of climate variability on agricultural productivity, especially for rain-fed farming. They emphasize the need for climate-smart agricultural practices and inform policies aimed at supporting smallholder farmers in similar agro-ecological zones.Received: 2024-11-29 Revised: 2025-04-04 Accepted: 2025-05-31 Published: 2025-07-31